Functional status and quality of life in older patients with advanced esophageal squamous cell cancer receiving second-line nivolumab ± ipilimumab therapy: a post hoc analysis of the phase 2, multicenter RAMONA study - Li, Moying; Meindl-Beinker, Nadja M.; Maenz, Martin; Betge, Johannes; Schulte, Nadine; Zhan, Tianzuo; Hofheinz, Ralf-Dieter; Vogel, Arndt; Angermeier, Stefan; Bolling, Claus; de Wit, Maike; Jakobs, Ralf; et al. (Journal of geriatric oncology, 2024)
Introduction - The phase 2 RAMONA study demonstrated that second-line nivolumab ± ipilimumab immunotherapy was feasible and effective in older patients with advanced esophageal squamous cell cancer (ESCC). Here, we presented results from functional status (FS) and quality-of-life (QoL) analyses. - Materials and Methods - Patients aged ≥65 years with advanced ESCC and disease progression following first-line therapy were enrolled for study treatment with nivolumab ± ipilimumab. Geriatric assessments (GA) consisting of G8 and GoGo/SlowGo evaluation, and quality of life (QoL) assessments with EORTC QLQ-C30 questionnaires were conducted at baseline and during the treatment. A post hoc analysis was performed to compare therapy efficacy, toxicity, and QoL between age groups (≥70 years vs. <70 years) and functionality groups (G8 > 14 vs. ≤14 and GoGo vs. SlowGo). - Results - In 66 treated patients with a median age of 70.5 years, older patients had non-inferior overall survival and tumor response compared to younger patients, with no increased treatment-related adverse events. Fitter patients (G8 > 14, GoGo) had a clinically, yet not statistically significant, survival advantage than less fit patients (G8 ≤ 14, SlowGo) patients. Moreover, FS by G8 and GoGo/SlowGo significantly correlated with QoL. Overall, QoL was impaired at baseline but remained stable in all scales over the course of immunotherapy. - Discussion - The administration of nivolumab ± ipilimumab second-line immunotherapy in older patients with ESCC did not show age-dependent effects and maintained QoL. GA could identify functional deficits and limitations of QoL and should be implemented in the context of immunotherapy. ClinicalTrials.gov: NCT03416244.